Layanan Bimbingan Kelompok Teknik Diskusi dalam Mengembangkan Regulasi Diri Belajar pada Siswa Kelas X SMA Negeri 2 Pemalang - Ita Ayu Fransiska; Arri Handayani; G. Rohastono Ajie (Journal on Education, 2023)
The main problem studied is the Discussion Technique Group Guidance Service in Improving Learning Self-Regulation in Class X Students of SMA Negeri 2 Pemalang. The research method used is true experimental with pretest-posttest control group design. The population in this study were all students of class X SMA Negeri 2 Pemalang, totaling 144 students consisting of 4 classes. The sampling technique used is cluster random sampling technique. The analysis used to test the validity is the product moment and reliability using the alpha formula. The final conclusion based on the calculation of the t-test obtained tcount of 11.072 while ttable with db(n1 + n2) – 2 = (12+12)-2=22 and a significant level of 5% (0.05) of 1.73 (see table t ). Because tcount>ttable, namely 11.072>1.73, it can be interpreted as larger, so Ha is accepted. It can be concluded that there are differences in the increase in learning self-regulation in the experimental group after being given treatment for three times using group guidance with discussion techniques. So it can be concluded that group guidance with discussion techniques can improve the learning self-regulation of class X students of SMA Negeri 2 Pemalang. Then the working hypothesis (Ha) which reads "group discussion technique guidance services can increase self-regulation of learning in class X SMA Negeri 2 Pemalang" is accepted with a significant level of 0.05. The suggestion that researchers can convey is that supervising teachers at schools provide advanced services with regard to self-regulation of learning.